Servant Leadership Style, Work Climate, Work Motivation Improved Handover Implementation - Hidarpa, Nana; Dewi, Sandra; Pamungkas, Rian Adi (Alta Dharma Publisher, 2025)
Background: Healthcare providers, particularly nurses, face the issue of enhancing the quality and consistency of communication along the healthcare chain, specifically at the transitory point or when interacting with healthcare officials. Safety problems can occur as a result of losses caused by failing to transmit patient information. Objective: The study seeks to examine the impact of characteristics related to servanter leadership style, working climate, and work motivation on the implementation of handover. Method: This research employs a quantitative study which is the cross-sectional study. The participant selected for this study was a nurse in a leadership position in a hospital unit, and the total number of respondents was 72. The research data was collected by questionnaire responses and analyzed using Structural Equation Modeling (SEM) techniques with the assistance of the SEM PLS application. Result: The findings of this study indicate that 1) Servant leadership, work climate, and work motivation together influence the implementation of handover. 2) Servant leadership has a positive and significant influence on work motivation; 3) Work climate has a positive and significant influence on work motivation; 4) Work motivation has a positive and significant influence on handover implementation; 5) There is no influence of servant leadership on handover implementation; 6) Work climate has a positive and significant influence on handover implementation. Conclusion: The integration of servant leadership, organizational climate, and work motivation is essential for the effective implementation of handovers